2022
DOI: 10.1093/bjsopen/zrac097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-hepatectomy liver failure on morbidity and short- and long-term survival after major hepatectomy

Abstract: Background Post-hepatectomy liver failure (PHLF) is one of the most serious postoperative complications after hepatectomy. The aim of this study was to assess the impact of the International Study Group of Liver Surgery (ISGLS) definition of PHLF on morbidity and short- and long-term survival after major hepatectomy. Methods This was a retrospective review of all patients who underwent major hepatectomy (three or more liver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The authors also found that all complications were significantly more frequently after major hepatectomy. Despite some differences in definitions, our results are similar to those reported in other studies on complex hepatic surgical interventions in patients with CRLM ( 30 - 33 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The authors also found that all complications were significantly more frequently after major hepatectomy. Despite some differences in definitions, our results are similar to those reported in other studies on complex hepatic surgical interventions in patients with CRLM ( 30 - 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…When we used HBS as the only preoperative assessment, and calculated the FLR-V values retrospectively, we found that 17 patients (21.3%) underwent successful surgery, despite a FLR-V <30%, even after LVD ( Table 3 ). We chose a FLR-V cut-off of 30%, like in other studies on patients with CRLM, to take into account the possible effect on liver function of prolonged chemotherapy prior to surgery ( 33 , 34 ). Patients with FLR-V <30% and HBS results above the cut-off had postoperative outcomes similar to patients with concordant HBS and volumetry.…”
Section: Discussionmentioning
confidence: 99%
“…More extensive liver resection, specifically major hepatectomy, was associated with the highest risk of morbidity and mortality in this study, predominantly due to liver insufficiency, consistent with previous data on this procedure for other tumour types. 24 It was not possible to draw any conclusions regarding the benefit of segment IVb/V resections over wedge resections in this study, as the exact extent of resection performed in each of these two procedures in practice may be imprecise. Our findings correlating extent of resection with increased morbidity would suggest that, where appropriate, the least extensive liver resection necessary to achieve clear margins should be performed.…”
Section: Discussionmentioning
confidence: 88%
“…Presently, the ISGLS PHLF criteria are the most frequently used in literature to define PHLF. Several aspects of the ISGLS criteria have been discussed, such as the potentially lacking clinical relevance of grade A 10 , 11 and that the criteria do not contain a distinction between primary and secondary liver failure 1 . A major problem of the definitions and predictive models mentioned above is their time point of applicability.…”
Section: Definitions and Epidemiologymentioning
confidence: 99%